Higher precipitation storage efficiency in nongrowing season ensures the success of dryland rain‐fed agricultural system. (2nd July 2020) - Li, Ming; Zhang, Kaiping; Qin, Rongzhu; Wan, Pingxing; Zhang, Wenjuan; Eldoma, Ibrahim M.; Zhang, Feng; Li, Fengmin
Abstract: In arid and semi‐arid regions, ridge‐furrow with plastic mulch (RFM) is an innovative approach to promote crop productivity and enhance food security. The long‐term effect of the RFM system on soil water is not known. A 7‐yr maize ( Zea mays L.) field experiment was conducted between 2012 and 2018 in the Chinese Loess Plateau to estimate the spatial and temporal variation of soil water. The objectives were to (a) understand how RFM affects soil water status during and between growing seasons; and (b) investigate whether RFM causes the formation of dry soil layers and threaten the sustainability of the agricultural system. In the nongrowing season, the average precipitation storage efficiency (PSE) of the plastic mulching treatment was 78.2%, compared to just 17.7% for no film mulching treatment. Higher PSE means that the RFM system stored more precipitation during the nongrowing season. In addition, 2‐ and 5‐m soil profile water status showed that the film mulching did not overuse deep soil water and would not lead to the formation of dry soil layers. Our research indicated that the RFM was beneficial for increasing crop production and sustainability of agriculture in semi‐arid regions. Higher PSE during the nongrowing season played an important role in the success of RFM system. We recommend that farmers adopted year‐round plastic mulch management method to make fuller use of water resources.